Coronavirus and Cardiovascular System - Parekh, Sandeep; Talwar, Kewal Krishan (Annals of the National Academy of Medical Sciences (India), 2020)
With the pandemic of COVID-19 infection spreading throughout the world leading to unprecedented serious burden on healthcare, our understanding of the virus continues to grow on a daily basis with the whole world united to find a vaccine/cure to combat the disease. Clinical experience with growing number of cases has provided us with insight into the pathophysiology of the disease and the various systems of the body it affects. The growing experience shows that cardiovascular complications occur in significant number of cases and contribute to increased mortality. The complications and mortality is also higher in those with pre-existing cardiovascular disease. The pathogenesis of increased cardiac complications is possibly related to the action of virus surface spike proteins through ACE2 receptors expressed in the myocardium. Although various drugs/therapies are being tried currently, no effective therapy is still available. It is emphasized that those with existing cardiac disease should optimally take their medicines, and religiously follow preventive measures like social distancing, self-isolation and hand hygiene.
Keywords: coronavirus; COVID-19; cardiovascular disease